FAMILY SUPPORT AND LIFEQUALITY OF KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS IN HOSPITAL - Hesti Dian Nirmalasari; Noor Hidayah; Umi Faridah ((IJP) Indonesia Jurnal Perawat, 2025)
Chronic Kidney Failure co, commonly known as CKD, is a condition in which the kidneys experience long-term damage. Patients with chronic kidney failure undergoing hemodialysis have a lower quality of life compared to the general population. Family support is one factor influencing patients' quality of life. The general objective of this study is to determine the relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at RST Tk. II 04.05.01 dr. Soedjono Magelang. This study uses a correlational research design. The population in this study consists of chronic kidney failure patients undergoing hemodialysis at RST Tk. II dr. Soedjono Magelang, with an average of 72 patients over six months.The sampling technique used was accidental sampling, with 46 respondents. Data collection was conducted using questionnaires. Bivariate analysis was performed using the Spearman Rank correlation test. The independent variable in this study is family support, measured using the Family Support Instrument. In contrast, the dependent variable is quality of life, measured using the World Health Organization Quality of Life (WHOQOL) instrument. The research was conducted from January to February 2025. The Spearman Rank statistical test results indicate a significant relationship between family support and quality of life in chronic kidney failure patients undergoing hemodialysis, with a p-value = 0.000. The correlation direction is positive, with a strong correlation strength (r = 0.628).In conclusion, the lower the family support, the worse the patient's quality of life, and conversely, the better the family support, the higher the patient's quality of life. It is recommended that families provide better emotional and practical support to chronic kidney failure patients to improve their quality of life during hemodialysis.